2017
DOI: 10.1177/1177180117729854
|View full text |Cite
|
Sign up to set email alerts
|

Exploring autism and music interventions through a First Nations lens

Abstract: This research project set out to examine the meaning of music for five First Nations children diagnosed with autism spectrum disorder in British Columbia, Canada. A pan-tribal framework within an Indigenist research paradigm was used. Data were collected during visits in 2013 and 2014. Five First Nations children with different tribal affiliations and living locations, their families, and professionals were engaged in the project. Methods were conversations, observations, filmed observations, interventions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…Small sample size. Lindblom, 2017 (Canada) [ 68 ] D Article: Exploring autism and music interventions through a First Nations lens. Qualitatively explored the meaning, purpose and use of music for First Nations children with ASD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small sample size. Lindblom, 2017 (Canada) [ 68 ] D Article: Exploring autism and music interventions through a First Nations lens. Qualitatively explored the meaning, purpose and use of music for First Nations children with ASD.…”
Section: Resultsmentioning
confidence: 99%
“…The studies described in six of the articles showed positive outcomes associated with the implementation and evaluation of programs designed specifically for Indigenous people with ASD, including improvements in personal (e.g., mood, self-esteem, relaxation, self-regulation, executive functioning; see Table 1 Bettag (Article A) [65] described a program that aimed to improve the developmental (cognitive and communication) outcomes of young children with developmental delay by strengthening parent/caregiver-child relationships and enhancing parenting and teaching skills, and used validated self-report scales and semi-structured observational assessments to measure outcomes. Other articles, Keightley et al (Article B) [66] and Lindblom (Articles C & D) [67,68] used theatre-based activities or traditional and non-traditional music in programs with Indigenous children with developmental impairment or ASD. According to observational reports from researchers, and anecdotal evidence gathered from interviews with participants and caregivers, the programs achieved increased inclusion, improved mood, and increased relaxation in participants.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Twenty-four articles were included. Seven articles explore identity and experiences of autistic Indigenous Peoples (Bailey & Arciuli, 2020;Kapp, 2011;Lindblom, 2014Lindblom, , 2017aLindblom, , 2017bSullivan, 2013;Travers et al, 2013). Ten articles explore autistic identity (Cooper et al, 2017;Cridland et al, 2014;DeNigris et al, 2018;Hughes, 2012;Kapp et al, 2013;MacLeod et al, 2013;Mogensen & Mason, 2015;Tan, 2018;Violeta & Langer, 2017;Winstone et al, 2014), five articles, Indigenous identity (Kahn et al, 2016;Kelley & Lowe, 2018;Kickett-Tucker et al, 2015;Tracey, 2012;Victor et al, 2016), and two articles, the inclusion and treatment of Indigenous students with a variety of disabilities (Bevan-Brown, 2013;Graham, 2012).…”
Section: Literature Searchmentioning
confidence: 99%
“…Membership approval and assignment are determined by agents with powers ascribed within colonial systems and structures. Indigeneity is defined by colonial legislative authority whereas "autism spectrum disorder (ASD)" is defined according to a medicalized framework of diagnostic criteria such as the American Psychiatric Association's (APA) Diagnostic and Statistical Manual of Mental Disorders or DSM (Bailey & Arciuli, 2020;Lindblom, 2017a;Sullivan, 2013) or the World Health Organization's International Classification of Functioning, Disability and Health.…”
Section: Identity Categorization and Controlmentioning
confidence: 99%
See 1 more Smart Citation